Marketing Strategy So that Buyers Immediately Decide to Buy On Tiktok - Diana Novita; Roy Budiharjo; Novawiguna Kemalasari; Muhammad Laras Widyanto; Sri Kurniawati (PT FORMOSA CENDEKIA GLOBAL, 2022)
The right marketing strategy should match the media you use. In particular, marketing activities can now be performed through a variety of media platforms, so this condition requires caution when planning marketing procedures. The motive of advertising is to trade the delivered cost that exists as many consumers as feasible, as regularly as feasible in order that consumers earnings and dealers’ earnings, so to